Mitos Dewi Hariti di Pura Candi Dasa Desa Bugbug Karangasem; Analisis Struktur, Fungsi dan Makna - Dwi Andini, Made; Nala Antara, I Gde (Humanis, 2018)
The title of this paper is “Mythical of Dewi Hariti in Candi Dasa Temple, Bugbug Village, Karangasem; Analyzeof Structure, Function and Meaning”. This paper is using structural theory, function theory and semiotics theory. The aims of this paper is to destribe narrative structure in Dewi Hariti’s mythical in Candi Dasa Temple and analysis the function and the meaning tht contained in Dewi Hariti’s mythical in Candi Dasa Temple. The step of provision the data are using method of interview and method of observation assisted with recording technique and take a note, is making a note for the important things that got from the observation. And then, we analyze the data by quali tative technique. In this stage, is supported by analytis dessritive method at the presentation stage of the data analysis the method is used informal method. Data source is using primary data and secondary data. The narrative structure in Dewi Hariti’s mythical in Candi Dasa Temple, Bugbug Village, Karangasem. There are 7 structure, synopsis, incident, plot, figures, theme, mandate and background. The function contained in Dewi Hariti’s mythical in Candi Dasa Temple are religious meaning and culture meaning.